Correlation between 5-HT, Hcy and the incidence and severity of autism in children: Autism cases in children and correlation with 5-HT - Li Xiaoxue, (Cellular and Molecular Biology, 2023)
This experiment was conducted to investigate the effects of serotonin or 5-hydroxytryptamine (5-HT) and homocysteine (Hcy) levels on the incidence and severity of autism in children. For this aim,120 autistic children were selected as the study group, and 120 children who took early psychological intervention were included in the study group I, and 120 children who took late psychological intervention were included in study group II. 120 non-autistic children hospitalized in the same period were selected as the control group. The levels of serotonin and Hcy were compared between the two groups. At the same time, the effects of different levels of serotonin and Hcy on the severity of autism in children were compared. Results showed that there were significant differences in 5-HT level, Hcy level, cesarean section, breast milk mode, premature delivery, vitamin B12 level, birth weight and early illness between study group I and control group, and between study group II and control group (all P < 0.01). The ASD score growth rate, ASD score change rate, 5-HT change rate and complications of study group I were lower than those of study group II, but the cure rate was significantly higher than that of study group II (P < 0.01). 5-HT, breast feeding, Hcy, vitamin B12 level, febrile convulsion and traumatic brain injury were the main risk factors for children with autism, while the psychological intervention was the main protective factor, which had a significant positive impact on the severity of children with autism (p < 0.05). 5-HT and Hcy levels have significant predictive effects on the development of children with autism and can be used as predictive indicators for the development of autism. In conclusion, 5-HT, feeding mode, Hcy, vitamin B12 level and febrile convulsion are the main risk factors for autism in children, and there are significant correlations.